Melorheostosis: The Incidental Finding of a Rare Bone Dysplasia in the Mandible on Panoramic and CBCT Images - A Case Report - Prasanthi Sitaraman; Ravleen Nagi; Arvind Muthukrishnan (Journal of Indian Academy of Oral Medicine and Radiology)
Melorheostosis or osteosclerotic bone dysplasia is a rare bone dysplasia that manifests as hyperostosis of bone and usually affects appendicular skeleton, and craniofacial involvement is rare. The diagnosis is based on clinical and the radiographic features. The typical radiographic feature that has been reported is the “dripping candle wax or flowing candle wax” pattern as seen in our case. We present a case of craniofacial melorheostosis, diagnosed incidentally when the patient was referred for dental implant assessment to the department of Oral and Maxillofacial Radiology.